Azacitidine-Induced Interstitial Pneumonitis. (September 2016) - Verriere, Benjamin; Ferreira, Vanessa; Denis, Eric; Zahreddine, Khaled; Deletie, Emmanuelle; Quinsat, Denis; Re, Daniel
Abstract : Azacitidine is a demethylating and cytotoxic drug for the treatment of adult patients with (1) myelodysplastic syndromes, (2) chronic myelomonocytic leukemia, and (3) acute myeloid leukemia who are not eligible for induction treatment or hematopoietic stem cell transplantation. Widely described in the literature, the main adverse events are hematotoxicity, digestive toxicity, asthenia, cutaneous toxicity, and infections such as neutropenic sepsis and pneumonia. The pivotal phase III comparative and supporting studies did not point out interstitial pneumonitis as a significant adverse event. Rare clinical data from literature report interstitial lung disease secondary to azacitidine administration, which should therefore be considered as a serious potential adverse event. We, herein, report a case of an 86-year-old white woman with acute myeloid leukemia and azacitidine-induced interstitial pneumonitis.